2020
DOI: 10.3389/fphar.2020.00763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tamsulosin Combined With Solifenacin on Lower Urinary Tract Symptoms: Evidence From a Systematic Review, Meta-Analysis, and Trial Sequential Analysis of Randomized Controlled Trials

Abstract: This study is aimed to systematically evaluate the efficacy of tamsulosin combined with solifenacin and provide clinical evidence for treatment of benign prostatic hyperplasia (BPH) with lower urinary tract symptoms (LUTS). PubMed, Cochrane Library, EMBASE, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, and Wanfang data information service platform were searched to select randomized controlled trials (RCTs) of tamsulosin combined with solifenacin in the treatment of BPH with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…The combination of tamsulosin and solifenacin rapidly decreased the total International Prostate Symptom Score (IPSS), Overactive Bladder Symptom Score (OABSS), and quality of life (QoL) scores during a short follow-up period (≤ 3 months) in patients with LUTS/BPH without increasing the risk of dysuria. 15 Large randomized controlled trials suggest that the combination of an alpha blocker and an ACH is well tolerated and has significant efficacy in men with both voiding and storage LUTS. 16 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…The combination of tamsulosin and solifenacin rapidly decreased the total International Prostate Symptom Score (IPSS), Overactive Bladder Symptom Score (OABSS), and quality of life (QoL) scores during a short follow-up period (≤ 3 months) in patients with LUTS/BPH without increasing the risk of dysuria. 15 Large randomized controlled trials suggest that the combination of an alpha blocker and an ACH is well tolerated and has significant efficacy in men with both voiding and storage LUTS. 16 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…Prostate volume usually correlates with the severity of LUTS, and transitional zone volume is the main contributor to the total prostate volume growth, which is suggested to be closely related to the severity of LUTS/BPH 15,16 . Although the assigned patients in the study group had a higher average prostate volume, the comparable effectiveness was shown in IPSS and QoL index with the control group scores.…”
Section: Discussionmentioning
confidence: 89%